Sport and postcolonialism (Global sport cultures, 2003)
Sport was a major tool of colonial power, and postcolonialism manifests itself in the modern sporting world in several ways, including the huge number of world class athletes from former European empires and the exploitation of child-workers in postcolonial nations by the sporting goods industries. Many former colonial states place considerable importance on elite sport as a form of representation, yet a small number of such states oppose sport in its western form. This book explores the wealth of issues and experiences that comprise the postcolonial sporting world and questions whether sport can act as a form of resistance in postcolonial states and, if so, how such resistance might manifest itself in the rule-bound culture of sport. [from publisher's advertisement].